Evidence for planetary hypothesis for PTFO 8-8695 b with five-year optical/infrared monitoring observations. (20th February 2020) - Tanimoto, Yuta; Yamashita, Takuya; Ui, Takahiro; Uchiyama, Mizuho; Kawabata, Miho; Mori, Hiroki; Nakaoka, Tatsuya; Abe, Taisei; Itoh, Ryosuke; Kanda, Yuka; Kawaguchi, Kenji; Kawahara, Naoki; et al.
Abstract: PTFO 8-8695 b (CVSO 30 b) is a young planet candidate whose host star is a $\sim\!\!{2.6}$ -Myr-old T-Tauri star, and there have been continuous discussions about the nature of this system. To unveil the mystery of this system, we observed PTFO 8-8695 for around five years at optical and infrared bands simultaneously using the Kanata telescope at the Higashi-Hiroshima Observatory. Through our observations, we found that the reported fading event split into two: deeper but phase-shifted "dip-A" and shallower but equiphase "dip-B". These dips disappeared at different epochs, and then, dip-B reappeared. Based on the observed wavelength dependence of dip depths, a dust clump and a precessing planet are likely origins of dip-A and B, respectively. Here we propose "a precessing planet associated with a dust cloud" scenario for this system. This scenario is consistent with the reported change in the depth of fading events, and even with the reported results, which were thought to be evidence against the planetary hypothesis.